Expression Of Stress Response Genes In Mud-Dwelling Stinging Catfish Heteropneustes Fossilis During Exposure To A Drying Mud-Bed (Applied Biological Research, 2020)
The natural habitats of Indian catfish (Heteropneustes fossilis) are generally  known for less oxygen and most often polluted water bodies. The present  study was aimed to understand the adaptability in terms of antioxidant  defense mechanism at transcript levels. The studyconsidered key  transcripts such as superoxide dismutase 2 (sod2), catalase (cat), glutathione  peroxidase 4 (gpx4), and heat shock protein 70 (hsp70), heat shock cognate  70 (hsc70), hypoxia inducible factor 1alpha (hif1a) of the catfish exposed to  a drying mud-bed while dwelling inside mud-peat under semidry conditions  for 15, 30 and 45 days. The study revealed that desiccation stress triggered  complicated oxidative stress. The cat, sod2 and gpx4 and hsp70 mRNA  expressions significantly up-graded in the mud-dwelled fish. Further, mud dwelling also resulted in significant increase in the expression of hif1α in  gills and muscle of fish after 30 days, suggesting its role as a vital regulator  that carries out important alterations in gene expression under hypoxic  stress. Collectively, the observations suggested that stress condition resulted  in the development of oxidative stress, and H. fossilis was able to respond  through alterations in stress responsive genes to survive semi-dry  conditions.
Keywords: Desiccation; hypoxia; hif1α; reactive oxygen species